Academician I.H. Aleksandrov’s contribution to the irrigation problem solution of the Central Asian lands (the beginnings of the ХХ century) - Isaienko, O. I. (History of science and technology, 2013)
In the article the contribution of the academician I.H. Aleksandrov in solving the irrigation problems of the Central Asian lands at the beginning of the ХХ century has been analyzed. I.H. Aleksandrov’s works of this period and direction have been considered by the author as a pre-flow to his later projects for large hydro-power plants (including in the Central Asia). Conducting researches in the Syrdar’ia river water-shed, Ivan Havrylovych Aleksandrov apprehended the unique value of the central Asian rivers as a powerful source for receiving cheap electric energy.